Letter to editor of the journal «Orthopedics, Traumatology and Prosthetics» - Goloborodko, S. A. (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Letter to editor of the journal «Orthopedics, Traumatology and Prosthetics»